Dual vocational education and training in Austria, Germany, Liechtenstein and Switzerland : comparative expert study ; full study - Bliem, Wolfgang [Verfasser]; Petanovitsch, Alexander [Verfasser]; Schmid, Kurt [Verfasser] (My University, 2016)
"The dual vocational education and training systems in Germany, Liechtenstein, Austria and Switzerland have evolved over time and are considerably influenced by the economic framework conditions and the historical development process in the country in question. They are similar to each other in many respects. This includes the fact that they are not the result of deliberate planning but rather are the outcome of a complex historical process. Dual vocational education and training in all four countries of comparison is understood as VET which takes place in at least two places of learning (therefore dual), i.e. on the job, in particular at the workplace in a company and off the job, in particular at VET school (Berufsschule, Berufsfachschule) and in VET centres. It leads to a full vocational qualification and is therefore also a programme which lasts for several years." (excerpt; BIBB-Doku)
Keywords: S 1 Stufen der Berufsbildung; S 1.3 Berufliche Erstausbildung; S 1.5 Weiterbildung; I 2.2.1 Westeuropa; I 2.1 Deutschland; Berufsbildung; Berufsbildungssystem; Duales System; Historische Entwicklung; Transfer; Berufliche Weiterbildung; Arbeitsmarkt; Berufsausbildung; Internationaler Vergleich; Alpenländer; Liechtenstein; Schweiz; Österreich; Bundesrepublik Deutschland